Chemodialysis of organic acids using ABPBI-based hollow fiber membranes - Gawas, Saroj; Alladi, Lavanya; Kharul, Ulhas K. (Journal of Membrane Science, 2024)
Organic acids are a class of essential commodity chemicals used in various industries. Their production methods are shifting from conventional chemicals to fermentation, driven by green process strategies, environmental regulations, cost feasibility, etc. Separating formed acid from the fermentation broth is a primary technological barrier. Conventional methods are complex and impose environmental issues. A promising approach, `Chemodialysis,' capable of transforming the techno-economical feasibility of acid recovery scenario by reducing the number of steps, needs further investigation. This work evaluates scalable hollow fiber membranes based on poly(2,5-benzimidazole) (ABPBI) for chemically assisted dialysis, viz., Chemodialysis. Sorption analyses of commercially significant organic acids (acetic, lactic, and glycolic acid) and nonacidic solutes (NaCl and glucose) were performed using conventional flat sheet samples to assess their role in governing permeation characteristics. The transport properties of acids in the presence of NaCl and glucose as co-solutes were analyzed using hollow fiber membranes. The high selectivity of acid over nonacidic solutes ranges from 400-22,400, coupled with high acid permeability, enhances the applicability of Chemodialysis for the separation of acids using hollow fiber membranes. The fluxes of acids (acetic, glycolic, and lactic) through dense, similar to 100 mu m thick, scalable hollow fiber membranes ranging from 10.9 to 13.12 g/m(2)h are highly appreciable.
Keywords: 5-benzimidazole); Acid separation; Chemodialysis; Hollow fiber membranes; Organic acids; Poly(2